A simple, inexpensive and multi‐scale 3‐D fluorescent test sample for optical sectioning microscopies. Issue 11 (18th May 2021) - Olevsko, Ilya; Szederkenyi, Kaitlin; Corridon, Jennifer; Au, Aaron; Delhomme, Brigitte; Bastien, Thierry; Fernandes, Julien; Yip, Christopher; Oheim, Martin; Salomon, Adi
Abstract: Fluorescence standards allow for quality control and for the comparison of data sets across instruments and laboratories in applications of quantitative fluorescence. For example, users of microscopy core facilities can expect a homogenous and time‐invariant illumination and an uniform detection sensitivity, which are prerequisites for imaging analysis, tracking or fluorimetric pH or Ca 2+ ‐concentration measurements. Similarly, confirming the three‐dimensional (3‐D) resolution of optical sectioning microscopes calls for a regular calibration with a standardized point source. The test samples required for such measurements are typically different ones, they are often expensive and they depend much on the very microscope technique used. Similarly, the ever‐increasing choice among microscope techniques and geometries increases the demand for comparison across instruments. Here, we advocate and demonstrate the multiple uses of a surprisingly versatile and simple 3‐D test sample that can complement existing and much more expensive calibration samples: commercial tissue paper labeled with a fluorescent highlighter pen. We provide relevant sample characteristics and show examples ranging from the sub‐μm to cm scale, acquired on epifluorescence, confocal, image scanning, two‐photon (2P) and light‐sheet microscopes. Abstract : Pyranine‐labeled tissue paper, imaged upon 405‐nm epifluorescence excitation through a 455LP LP dichroic and 465LP emission filter. Objective ×20/NA0.25. Overlaid are the nor‐malised absorbance (dashed) and emission spectra (through line), respectively. In the present work, we show that this "primitive" and inexpensive three‐dimensional (3‐D) test sample is a surprisingly versatile and powerful tool for quality assessment, comparison across microscopes as well as routine metrology for optical sectioning techniques, both for research labs and imaging core facilities.